2014
DOI: 10.4103/2225-4110.124351
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of N-acetylcysteine and a Prostaglandin E1 Analog, Alprostadil, Against Hepatic Ischemia: Reperfusion Injury in Rats

Abstract: Ischemia–reperfusion (I/R) injury has a complex pathophysiology resulting from a number of contributing factors. Therefore, it is difficult to achieve effective treatment or protection by individually targeting the mediators or mechanisms. Our aim was to analyze the individual and combined effects of N-acetylcysteine (NAC) and the prostaglandin E1 (PGE1) analog alprostadil on hepatic I/R injury in rats. Thirty male Sprague-Dawley rats were randomly divided into five groups (six rats per group) as follows: Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
1
20
1
1
Order By: Relevance
“…More recent studies on animal small intestine and liver tissues have suggested a beneficial effect of PGE1 on ischemia/reperfusion injury …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…More recent studies on animal small intestine and liver tissues have suggested a beneficial effect of PGE1 on ischemia/reperfusion injury …”
mentioning
confidence: 99%
“…The hepatoprotective effects of prostaglandins were initially demonstrated in animal models, including dimethylnitrosamineinduced liver injury, (2) carbon tetrachloride-induced liver injury, (3) and ischemia/reperfusion injury. (4) An immunomodulatory effect has also been proposed for exogenous prostaglandins, based on animal models of polyarthritis in rats and systemic lupus erythematosus in mice. (5,6) A number of mechanisms have been proposed to explain the hepatoprotective effects of prostaglandins, (7)(8)(9)(10)(11)(12) which include the following:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that N-acetylcysteine attenuated I/R injury on liver and intestine in normothermic conditions 7,9,10 . In experimental hepatic ischemic injury, the treatment with the N-acetylcysteine, immediately before ischemia, preserved morphological architecture and tissue functionality during ischemia [8][9][10] .…”
Section: Introductionmentioning
confidence: 92%